Frequency of A1 and A2 alleles of the β-casein gene in cattle in the Cajamarca region of Peru - Becerra Quiroz, Antuanet Lissett (2025)
Background: Cow's milk β-casein has multiple genetic variants, the two most common of which are A1 and A2, which are encoded by the CSN2 gene. Evidence suggests that the A1 variant may negatively affect human health. Type A2 milk is a safer alternative for human consumption because it is easier to digest than A1. Aim: To determine the frequency of the A1 and A2 alleles of the β-casein gene in cattle. Methods: Blood samples were collected from 103 cattle (26 males and 77 females), 71 crossbred, 30 Simmental, 1 Jersey, and 1 Holstein. The selection prioritized females due to their economic value for milk production, reproductive potential, and capacity to replace cows of high genetic value, whereas males are intended for sale for meat production. Analysis of the A1 and A2 alleles of exon 7 of the CSN2 gene was carried out by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) using the restriction enzyme DdeI. Results: The heterozygous A1A2 genotype was the most frequent (50.5%, n = 52), followed by the homozygous A2A2 genotype (35.0%, n = 36) and A1A1 genotype (14.6%, n = 15). The results showed that 33.8% (26/77) of the females and 38.5% (10/26) of the males had the A2A2 genotype. Conclusion: PCR-RFLP genotyping allowed the genotypic frequencies of β-casein to be determined, with 33.8% and 38.5% A2A2 in females and males, respectively.